Strategi Marketing Mix Dalam Meningkatkan Penjualan Pada Usaha Toko Kue 3&4 Di Kota Mataram - Nadila Amelianti Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2026)
This study aims to analyze the Marketing Mix Strategy in increasing sales in the Toko Kue 3 & 4 in Mataram City. This research is descriptive qualitative by linking the independent variable to the dependent variable. Data collection techniques using observation, interviews, documentation. Research results Based on the evaluation results will then be described in a SWOT analysis diagram. The internal evaluation value shows a strength value of 1.38 - 0.96, which is 0.42 in the direction of the strength factor, and the external evaluation value shows the position of the up arrow or an opportunity of 1.61 - 0.95, which is 0.66 so that in the resulting IFAS, EFAS and SWOT matrices analysis, the recommended strategy to increase the competitiveness of Toko Kue 3&4 is the ST strategy, which is a strategy that supports diversification strategy, namely by using existing strengths to minimize the threats faced. This makes the marketing strategy that pays attention to the 4P's can take advantage of Instagram social media as promotion and WhatsApp communication as a messaging service or through renewable applications such as grab, gojek, etc. to increase sales for Toko Kue 3&4 Kota Mataram can be implemented for the development of Toko Kue 3&4 in Kota Mataram.